Translational implications of targeting annexin A2: From membrane repair to muscular dystrophy, cardiovascular disease and cancer - Victor G. Kayejo; Hannah Fellner; Roshan Thapa; Peter A. Keyel (Clinical and Translational Discovery, 2023)
Abstract Background Annexin A2 contributes to several key cellular functions and processes, including membrane repair. Effective repair prevents cell death and degeneration, especially in skeletal or cardiac muscle, epithelia, and endothelial cells. To maintain cell integrity after damage, mammalian cells activate multiple membrane repair mechanisms. One protein family that facilitates membrane repair processes are the Ca2+‐regulated phospholipid‐binding annexins. Body Annexin A2 facilitates repair in association with S100A10 and related S100 proteins by forming a plug and linking repair to other physiologic functions. Deficiency of annexin A2 enhances cellular degeneration, exacerbating muscular dystrophy and degeneration. Downstream of repair, annexin A2 links the membrane with the cytoskeleton, calcium‐dependent endocytosis, exocytosis, cell proliferation, transcription, and apoptosis to extracellular roles, including vascular fibrinolysis, and angiogenesis. These roles regulate cardiovascular disease progression. Finally, annexin A2 protects cancer cells from membrane damage due to immune cells or chemotherapy. Since these functions are regulated by post‐translational modifications, they represent a therapeutic target for reducing the negative consequences of annexin A2 expression. Conclusion Thus, connecting the roles of annexin A2 in repair to its other physiologic functions represents a new translational approach to treating muscular dystrophy and cardiovascular diseases without enhancing its pro‐tumorigenic activities.